Effect of interface traps on the different conduction mechanisms of MISHEMT from 200 K to 450 K - Perina, Welder F.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
In this work, the effect of the interface traps on the different conduction mechanisms of a Metal Insulator Semiconductor High Electron Mobility Transistor (MISHEMT) operating in multiple temperatures (from 200 K to 450 K) is evaluated through High Electron Mobility Transistor (HEMT) and Metal Insulator Semiconductor Field Effect Transistor (MISFET) numerical simulations. The interface traps of the MISFET poses barely any effect on the threshold voltage. For the HEMT, however, the behavior with traps enabled is basically the opposite when the traps are disabled. Combining the opposite behaviors of the threshold voltage curves of the MISFET and HEMT as a function of temperature, gives a possible explanation of the threshold voltage rebound effect observed in MISHEMT.
Keywords: GaN; MISHEMT; multiple conductions; temperature; threshold voltage